Developing the Hall of Human Origins - Smith, Shelley L., author.
1 online resource.
Keywords: "This book focuses on the development of the National Museum of Natural History's David H. Koch Hall of Human Origins. As one of the most visited human evolution exhibits in the world and the largest such exhibit in the United States of America, it has tremendous influence on public perception and knowledge of human evolution. The chapters explore how this exhibit came about, how it has changed since opening, and the associated educational and public outreach activities of members of the Smithsonian's Human Origins Program. The author uses the term 'adaptive resilience' to describe a central theme of the exhibit, our species' adaptation to changing environments as a key feature of our success, and to refer to the resilience of Richard B. Potts in creating his vision for the hall. Contextual sections situate the hall's development within the history of paleoanthropology, the politics of evolution and climate change, and African contributions. The book will be of particular interest to scholars of anthropology and museum studies as well as the history of science and science communication"--